Examining the Divergence Across Self-report and Official Data Sources on Inferences About the Adolescent Life-course of Crime - Kirk, David S. (Journal of quantitative criminology, 2006)
Both self-report and official crime data have known limitations, leading to the critical question as to whether inferences about the adolescent life-course of crime are different across these data sources. Using both official and self-report arrest data on a sample of subjects drawn from the Project on Human Development in Chicago Neighborhoods (PHDCN) longitudinal cohort study, this paper examines the extent to which individual age-arrest curves are comparable across these data sources. Particular attention is given to examining whether criminal career dimensions, namely participation, frequency of arrest, age of onset, and continuity in behavior, are similar across data sources. Additionally, this paper examines whether the key predictors of youth crime (e.g., family processes, peer influence, and neighborhood disadvantage) function similarly across measurement types. Findings reveal that a sizable number of youth self-report being arrested without having a corresponding official arrest record, and a sizable proportion of those youth with an official arrest record fail to self-report that they had been arrested. Despite significant differences across the two arrest measures on many criminal career dimensions, the effects of family supervision, parent–child conflict, and neighborhood disadvantage operate similarly across data types.